New Insights into Mycobacterium bovis Prevalence in Wild Mammals in Portugal. Issue 5 (7th December 2014) - Matos, A. C.; Figueira, L.; Martins, M. H.; Pinto, M. L.; Matos, M.; Coelho, A. C.
Summary: A survey to determine the prevalence of Mycobacterium bovis in wild mammals in Portugal was conducted by testing samples from hunted animals and those found dead between 2009 and 2013. In this study, we investigated 2116 wild mammals. Post‐mortem examinations were performed, and tissues were collected from wild mammals representing 8 families and 11 different species, with a total of 393 animals analysed. Cultures were performed, and acid‐fast isolates were identified by PCR. Tissues were also screened for Mycobacterium bovis by directly extracting DNA and testing for the Mycobacterium bovis ‐specific sequences. Mycobacterium bovis prevalence was 26.9% (95% CI: 22.8–31.5%). Mycobacterium bovis was recorded in 106 of the 393 studied species: prevalence by species were 26.9% (95% CI: 16.8–40.2%) in red foxes, 20.0% (95% CI: 7.0–45.2%) in Egyptian mongooses, 21.4% (95% CI: 16.2–27.7%) in wild boar and 38.3% (95% CI: 29.9–47.4%) in red deer. Mycobacterium bovis infection was detected in six of eight taxonomic families. For some species, the small sample sizes obtained were a reflection of their restricted range and low abundance, making estimates of infection prevalence very difficult (1 beech marten of 4; 1 Eurasian otter of 3; 2 common genet of 3). Infection was not detected in European badgers, hedgehog, wild rabbits and hare. The results of this study confirm the presence of Mycobacterium bovis infection in wild carnivores in Portugal.